Sharenting Oleh Pasangan Selebritis di Indonesia: Studi Netnografi Pada Akun Instagram @ameenaatta - Zaneti Sugiharti (Dinasti Review, 2024)
The presence of social media gave rise to a phenomenon called sharenting, namely the activity of sharing parenting or family life with the community. The culture of sharing cannot be separated from the influence of celebrities who share content related to their personal lives and that of their children. Parents' uploads may not necessarily get the consent of the child. In relation to sharenting activities, this study looks at how sharenting culture is carried out by a pair of celebrities towards their children to increase their celebrity capital. The results found that the practice of sharenting is carried out to instill identity with certain values of parents towards children on children's social media, so that children become an extension of the parents' hands to maintain existence and increase their celebrity capital.